Learning by Doing and Protection of an Infant-Industry - Eugenio J. Miravete (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
This paper addresses an optimal tariff design to protect an infant-industry in the presence of learning effects. Firms decide how much to produce, taking into account learning effects induced by their current production, while the government decides on the level of tariff protection. In order to include different levels of bargaining power for each group of agents, each component of the welfare function is weighted with these weights taken as given. We solve the symmetric case without spillovers and fixed cost reduction due to accumluated output. Assuming that domestic and foreign production are imperfect substitutes for each other but perfect substitutes within each group, we use a complete linear demand system to represent domestic consumers' preferences. The analytic Markov Perfect Equilibria of this game is derived by solving a linear-quadratic differential game. The optimal tariff policy is characterized and compared to Spain's tariff policy on Iron and Steel for 1913.
Keywords: 330